The Effect of Buginese Language Transfer on Students’ English Pronunciation: A Case Study at SMAN 4 Barru - Harun, Lisa Binti; Mujiyanto, Januarius; Faridi, Abdurrachman (Universitas Negeri Semarang, 2019)
Indonesia is a country consists of various cultures and possesses hundreds of native language. Therefore, in the process of l2 acquisition, the impact of L1 on English articulation certainly is seen as a tough obstacle for the Indonesian EFL learners. In SLA, it is known as language transfer. Buginese language as one of the native language existed in South Sulawesi also gave positive and negative transfer towards English pronunciation. It was proven through a qualitative case study employed towards 20 students from XI IPA 2 at SMAN 4 Barru. To obtain the data, several methods were undergone such as questionnaires, students’ recording, interview and observation. The results of the study showed that Buginese language gave major negative transfer towards vowels /ə/ and /æ/, diphthongs /ɪə/, /eə/, /ʊə/ and /əʊ/, consonants /p/, /f/, /ŋ/ and /n/, and also clusters skr/, /spl/ (initial), /sk/, and /bl/. Moreover, this language gave minor negative transfer towards long vowels /i:/, /ɑ:/, /ɔ:/, and /u:/ and vowels /ɒ/, also consonants /ʤ/, /ʒ/, /z/, /v/, /ð/, /θ/, /ʧ/, and /ʃ/. It did not give any transfer towards diphthongs /eɪ/ (initial), /aɪ/ (initial and final) and /aʊ/. Besides that, Buginese language also gave minor positive transfer towards; vowels /ʌ/, /ɪ/, /e/, /ʊ/ and /ɔ/, diphthongs /ɔɪ/, /eɪ/ (middle and final), and /aɪ/ (middle), and also consonants /b/, /d/, /g/, /h/, /k/, /l/, /m/, /r/, /s/, /t/, /w/ and /y/. Last, the role of the teacher in improving students’ pronunciation was considered lack and need to be improved.